Plastic Aesthetic Intuition: Literature to Represent Travel Persuasion - Dahal, Ram Prasad (Literary Studies, 2026)
The paper “Plastic Aesthetic Intuition: Literature to Represent Travel Persuasion” captures theories of various literature and literati and finds literature a representative means to persuade “aesthetic” and “intuition,” both of which are plastic. These are individually customized phenomena. The research study draws on the contributions of William Hazlitt, Longinus, T. S. Eliot, and Oscar Wilde, as well as environmental philosophy from Peter Miller, Donald Worster, and Holmes Rolston. Further, the environmental integrity aspects with the study of theories contributed by Baird J. Callicott, Holmes Rolston, and Michael Soulé are taken to support this research claim. Naturalism is concerned with the environment and human passion. Ideology, its forms, and what is inherent in nature and the human mind are mostly representative of expressions. This research blends ideas of Aristotle and Plato with the views, respectively, mimetic and idealistic. Postmodernism and the twenty-first century are taking the course by actors influenced by the mimetic and ideologies engrossed into an aesthetic conscience, which is so diverse, personalized, and customized by capitalism that it is being most plastic, blurring the aesthetic heritage blended within culture and nature. To provoke the thought emerged within the intuition while doing research, writing those blended ideas embraced by travel and the cause to persuade travelers is claimed: ‘aesthetic’ and ‘intuition’ both are plastic.